MakerMinds: An Exploratory Study of Making and Mindfulness Pedagogies - Edmundson, Joanne; Jenson, Jennifer (Canadian Journal of Education / Revue canadienne de l'éducation, 2022)
The purpose of this ethnographically informed research study was to explore the integration of making and mindfulness pedagogies in a single curricular intervention (“MakerMinds”) and, in particular, how making engages students in mindfulness content and encourages their independent use of mindfulness tools. Mindfulness programs have long been used to promote mental health in clinical and non-clinical settings. Related research with school-aged children is limited, however, and the problem of how to fully engage them in mindfulness programming remains unsolved. Here, we report on the experiences of 24 Grade 4 students in MakerMinds over an eight-week period. Qualitative data from multiple sources revealed a program successful in engaging students and encouraging their application of mindfulness tools as needed in their daily lives. It also positively impacted conceptual and experiential knowledge of mindfulness and developed students’ agentic awareness of themselves as problem-solving makers and nascent mindfulness practitioners.